Low rate of reoperations after acute type A aortic dissection repair from The Nordic Consortium Registry - Emily Pan; Tomas Gudbjartsson; Anders Ahlsson; Simon Fuglsang; Arnar Geirsson; Emma C. Hansson; Vibeke Hjortdal; Anders Jeppsson; Kati Järvelä; Ari Mennander; Shahab Nozohoor; Christian Olsson; et al. (Mosby Inc., 2025)
Objectives
To describe the relationship between the extent of primary aortic repair and the incidence of reoperations after surgery for type A aortic dissection.
Methods
A retrospective cohort of 1159 patients treated for type A aortic dissection at eight Nordic low- to medium-sized cardiothoracic centers from 2005 to 2014. Data were gathered from patient records and national registries. Patients were separately divided into 3 groups according to the distal anastomoses technique (ascending aorta [n = 791], hemiarch [n = 247], and total arch [n = 66]), and into 2 groups for proximal repair (aortic root replacement [n = 285] and supracoronary repair [n = 832]). Freedom from reoperation was estimated with cumulative incidence survival and Fine-Gray competing risk regression model was used to identify independent risk factors for reoperation.
Results
The median follow-up was 2.7 years (range, 0-10 years). Altogether 51 out of 911 patients underwent reoperation. Freedom from distal reoperation at 5 years was 96.9%, with no significant difference between the groups (P = .22). Freedom from proximal reoperation at 5 years was 97.8%, with no difference between the groups (P = .84). Neither DeBakey classification nor the extent of proximal or distal repair predicted freedom from a later reoperation. The only independent risk factor associated with a later proximal reoperation was a history of connective tissue disease.
Conclusions
Type A aortic dissection repair in low- to medium-volume centers was associated with a low reoperation rate and satisfactory midterm survival. The extent of the primary repair had no significant influence on reoperation rate or midterm survival.